Cash Waqf Acceptance Among Entrepreneurs in Kano Metropolis, Nigeria - Muhammad, Aliyu Dahiru; Alkassim, Jibril Lawan; Sulaiman, Sagir Muhammad (International Journal of Islamic Economics and Finance (IJIEF), 2023)
Cash waqf was introduced as an alternative for individuals who do not have an immovable asset but rather have the cash to donate as waqf. It can be observed, however, that Muslims in Kano State narrow their perception of waqf only to be in the form of a kind but not in cash. It is to say that public awareness and understanding of cash waqf are insignificant. Therefore, this study aims to assess factors influencing the intention to accept cash waqf among entrepreneurs in the Kano metropolis with particular reference to Singer Market. The study employed partial least square–structural equation modeling (PLS-SEM) and was theoretically guided by the Theory of Planned Behavior (TPB). Structured survey questionnaires were administered to 379 respondents whom were registered entrepreneurs in Singer Market based on a convenience non-probability sampling technique. Descriptive statistics using charts and tables were employed to analyze the demographic information, while data collected from the respondents were analyzed utilizing AMOS, version 21. The study uncovered that perceived behavioral control and religiosity significantly influenced the intention to accept cash waqf among entrepreneurs in Singer Market in Kano Metropolis, while awareness and attitude did not. This paper recommends that the management of the Kano State Zakat and Hubsi Commission (KSZHC) should establish sensitization programs to create awareness and promote cash waqf for the public to mobilize more potential waqf donors in the state.